2013
DOI: 10.1136/amiajnl-2012-001607
|View full text |Cite
|
Sign up to set email alerts
|

An end-to-end system to identify temporal relation in discharge summaries: 2012 i2b2 challenge

Abstract: The system achieved encouraging results, demonstrating the feasibility of the tasks defined by the i2b2 organizers. The experiment result demonstrates that both global and local information is useful in the 2012 challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 11 publications
0
50
0
Order By: Relevance
“…The CNN token-based model had similar performance as some of the one-tag temporal representations (Table 1( 3,4,5)). Removing the time expression entirely (Table 1(10)) did not hurt performance much, confirming that time expressions were not critical cues for within-sentence event-event relation reasoning (Xu et al, 2013). Thus, on the colon test set, we evaluated the contribution of encoding time expressions on the eventtime CNN model only.…”
Section: Evaluation Methodology and Resultsmentioning
confidence: 79%
“…The CNN token-based model had similar performance as some of the one-tag temporal representations (Table 1( 3,4,5)). Removing the time expression entirely (Table 1(10)) did not hurt performance much, confirming that time expressions were not critical cues for within-sentence event-event relation reasoning (Xu et al, 2013). Thus, on the colon test set, we evaluated the contribution of encoding time expressions on the eventtime CNN model only.…”
Section: Evaluation Methodology and Resultsmentioning
confidence: 79%
“…The backwards BIO tagger achieved an Fscore of 0.889 on the i2b2 Challenge data allowing for partial matches (the Overlapping column). The best performing system in the i2b2 Challenge (Xu et al, 2013) is shown in the last row, with an F1 score of 0.914, with an advantage on recall. Our best system performance would tie for 4th in the span matching part of that challenge, without tuning for that dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Our best system performance would tie for 4th in the span matching part of that challenge, without tuning for that dataset. While we incorporated features based on the best-performing similar system (Xu et al, 2013), including punctuation information, prepositions, and chunk information, these did not improve performance. Their paper described a larger system and did not contain enough detail on time expression extraction to replicate exactly (e.g., the Other Keywords section in the online supplement is not exhaustive and probably is important to their result).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges include extracting clinical events and relation classification, and identifying temporal relation between two events. Many research groups have participated and proposed technologies of natural language processing for medical texts [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%